2006
DOI: 10.1080/09500780608668707
|View full text |Cite
|
Sign up to set email alerts
|

Managing Bilingual Interaction in a Gujarati Complementary School in Leicester

Abstract: This paper focuses on teacher-student interaction in two Gujarati complementary school classrooms in one school in the East Midlands city of Leicester, UK. To date, little work has been published on interaction in complementary schools, and little is therefore known about the cultures of learning and teaching in such contexts. Our study of complementary schools in Leicester has shown how the classroom participants manage bilingualism and bilingual learning and teaching. One of the most noticeable features of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…A similar situation can be found in the burgeoning studies of CS in complementary schools. For example, Martin et al (2006) examined the issue of how bilingualism is managed in classroom interaction in a Gujarati complementary school in Leicester (UK) and reported that 'participants spontaneously juxtapose Gujarati and English in order to create learning/teaching opportunities' (2006, 5, our emphasis). Clearly, this idea of the spontaneous juxtaposition of languages implies a local-level view of language choice, or at least does not signal any status differential between the languages involved.…”
Section: Code-switching (Cs) In the Classroom: What Is Switched From?mentioning
confidence: 98%
“…A similar situation can be found in the burgeoning studies of CS in complementary schools. For example, Martin et al (2006) examined the issue of how bilingualism is managed in classroom interaction in a Gujarati complementary school in Leicester (UK) and reported that 'participants spontaneously juxtapose Gujarati and English in order to create learning/teaching opportunities' (2006, 5, our emphasis). Clearly, this idea of the spontaneous juxtaposition of languages implies a local-level view of language choice, or at least does not signal any status differential between the languages involved.…”
Section: Code-switching (Cs) In the Classroom: What Is Switched From?mentioning
confidence: 98%
“…As in the research of Martin et al (2006), we found that bilingual strategies, rather than Bengali alone, were often being used to help second and third generation pupils transfer understandings between languages. We then worked with the children's primary school teachers, bilingual assistants and the community teachers to devise tasks that children could do bilingually in mainstream school, drawing on children's knowledge from community class as well as linking with the mainstream literacy and numeracy curriculum.…”
Section: How Can Bilingual Learning Help Second and Third Generation mentioning
confidence: 74%
“…Research indicates that there is a significant relationship between language, culture and identity (Martin et al 2006;Tsolidis and Kostogriz 2008;Wu 2006). Most students in this study feel that learning Chinese is linked to their ethnic identity.…”
Section: Learning Chinese As a Marker Of Ethnic Identitymentioning
confidence: 98%